Impact of structural stability of cold adapted Candida antarctica lipase B (CaLB): in relation to pH, chemical and thermal denaturation1. Issue 26 (22nd March 2015) - Rabbani, Gulam; Ahmad, Ejaz; Khan, Mohsin Vahid; Ashraf, Mohd. Tashfeen; Bhat, Rajiv; Khan, Rizwan Hasan
<x xml:space="preserve">Abstract</x> The effect of pH on the conformational behavior of Candida antartica lipase B (CaLB) has been monitored by spectroscopic and calorimetric studies.